Meningkatkan Hasil Belajar Sosiologi Melalui Model Pembelajaran Berdiferensiasi - Thimotius Uas; Andreas Ande (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Kupang, 2025)
Differentiated learning is a teaching strategy designed to meet the diverse learning needs of students. This study aims to improve the sociology learning outcomes of Grade X Social Science students at SMA Negeri Sambet through the implementation of a differentiated learning model. The research method used was Classroom Action Research (CAR), carried out in two cycles, with each cycle consisting of two sessions followed by an evaluation. The research subjects consisted of 30 students. Data were collected through observation, interviews, learning outcome tests, and documentation, and analyzed using qualitative and quantitative descriptive techniques. The results showed an increase in students’ learning outcomes from the pre-cycle to Cycle II. The average pre-cycle score was 65.33, increasing to 80.75 in Cycle I and reaching 91 in Cycle II. The percentage of learning mastery also increased from 47% in the pre-cycle to 56% in Cycle I, and 87% in Cycle II. These findings indicate that the implementation of the differentiated learning model is effective in improving students’ sociology learning outcomes. Therefore, this model can be considered a relevant and applicable learning strategy for diverse classroom conditions.